Managing High Performance in an Organization by Means of Employee Value Proposition (Case Study in PT ISS indonesia) - Anastasia, Anastasia; Welly, John (The Indonesian Journal of Business Administration, 2013)
ISS Indonesia is a part of one of the worldâ€™s largest facility service groups. Established in 1996 in Jakarta, ISS Indonesia has now become a leading cleaning and facilities service company. ISS Indonesia has five main business namely property services, cleaning, office support, catering, and security services. With more than 57.00 employees at total and cleaning services area as the biggest business of the company, the concern at the moment is to gain better performance. An engaged employee is the key to gain performance. When the employees did not perform at their best, we have to assess the lacking point from the employees.. As this research focuses in non- financial measurement, Employee Value Performance is the proven model that could determine employee engagement. The idea of this model is to search for an improvement in various employee expectation areas : leadership, job, development opportunity, rewards, fair value performance, culture and values.The result shows that all areas of the six variables need improvement. In the end, the improvement needed falls into Five Areas of Improvements: assignment improvement, evaluation and rewards improvement, team improvement, leader improvement, and training improvement.Â Keywords: performance, Employee Value Proposition, improvement